New diagnosis myasthenia gravis and preeclampsia in late pregnancy. (26th February 2015) - Ozcan, John; Balson, Ian Frank; Dennis, Alicia T
Abstract : Myasthenia gravis is a chronic autoimmune disease of neuromuscular transmission resulting in fatigable skeletal muscle weakness. Preeclampsia is a multisystem disease of pregnancy which is characterised by hypertension and involvement of one or more organ systems. Both diseases are responsible for considerable morbidity and mortality for mother and fetus. The occurrence of both preeclampsia and myasthenia gravis in pregnancy is very rare, and conflicts arise when considering the optimal management of each disease.We present a case of a parturient who was newly diagnosed with both myasthenia gravis and preeclampsia in late pregnancy. Myasthenia treatment was started with prednisolone and pyridostigmine, and delivery was by caesarean section at 37 weeks gestation under spinal anaesthesia. Postnatally, the patient developed worsening of myasthenia and preeclampsia symptoms. We consider the anaesthetic implications for both diseases and describe our approach for the management of this case.